A rapid method for detecting specific amplified PCR fragments in microtiter plates. - Ortiz, A (1996)
A simple method is presented to circumvent laborious and time consuming electrophoretic separations of specific PCR amplification products. Specific target DNA is amplified using nucleotides labelled with DIG-dUTP or biotin-dCTP. The labelled PCR products are separated from unincorporated nucleotides or oligonucleotides by using a positively charged DEAE cellulose matrix. Amplification products are visualized directly in the matrix using immunoenzymatic methods or streptavidin-conjugated enzymes. The detection process can be carried out within 2 h, allows the processing of large sample sizes and can potentially be automated.